EVALUATION OF TECHNOLOGY ACCEPTANCE MODELS ON ADMISSION OF E-PROCUREMENT INFORMATION SYSTEMS (Case Study in The Office of Goods and Services Procurement Work Unit, - Haryati, Tati; Sukoharsono, Eko Ganis; Prasetya, Arik (Accounting Department,, 2019)
With the existence of e-Procurement as part of e-Government, it is expected to be able to realize the efficiency and effectiveness of the procurement of goods and services at the Jayawijaya Regency UKPBJ Office. This system is expected to be able to help accelerate development in Jayawijaya Regency so that it does not lag far behind other regions. The aims of study is to evaluate the acceptance of the e-Procurement system by using the Technology Acceptance Model (TAM) at the Jayawijaya Regency UKPBJ office. By using a descriptive qualitative purposive sampling, and snowballing sampling approach with 16 informants, the researcher used triangulation, member checking, the audit trail, and prolonged engagement in the field as a test of credibility. The study shows that the implementation of e-Procurement at the UKPBJ Office is in accordance with existing regulations even though it has not run optimally because of the five principles of procurement of goods and services used, namely efficient, effective, transparent, open, competitive, fair and accountable, only the principle of efficiency, transparent, open and accountable achieved